1999
DOI: 10.1074/jbc.274.14.9431
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative Binding of Smad Proteins to Two Adjacent DNA Elements in the Plasminogen Activator Inhibitor-1 Promoter Mediates Transforming Growth Factor β-induced Smad-dependent Transcriptional Activation

Abstract: Transforming growth factor ␤ (TGF␤) activates transcription of the plasminogen activator inhibitor type-1 (PAI-1) gene through a major TGF␤-responsive region (؊740 and ؊647) in the PAI-1 promoter. This process requires the Smad family of signaling molecules. Upon phosphorylation by the TGF␤ receptors, Smad2 and Smad3 homoligomerize and heteroligomerize with Smad4, translocate to the nucleus and activate transcription of TGF␤ responsive genes. Smad3 and Smad4 have been shown to bind to various sites in the PAI-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
112
0

Year Published

2001
2001
2003
2003

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 119 publications
(116 citation statements)
references
References 43 publications
4
112
0
Order By: Relevance
“…The probe was incubated with the isolated Smad4-Flag and then the complexes were electrophoresed. We observed a signi®cantly shifted band ( This band was not detected when we used a mutant probe in which SBE was changed to a sequence di erent from the consensus sequence (Stroschein et al, 1999) (data not shown). On the other hand, no band was detected when the probe was incubated and electrophoresed with the Flag-tagged form of P102L ( Figure 6, lane 4), indicating that P102L has lost the DNA-binding ability.…”
Section: Analyses Of the Dna-binding Ability Of Smad4p102lmentioning
confidence: 84%
See 2 more Smart Citations
“…The probe was incubated with the isolated Smad4-Flag and then the complexes were electrophoresed. We observed a signi®cantly shifted band ( This band was not detected when we used a mutant probe in which SBE was changed to a sequence di erent from the consensus sequence (Stroschein et al, 1999) (data not shown). On the other hand, no band was detected when the probe was incubated and electrophoresed with the Flag-tagged form of P102L ( Figure 6, lane 4), indicating that P102L has lost the DNA-binding ability.…”
Section: Analyses Of the Dna-binding Ability Of Smad4p102lmentioning
confidence: 84%
“…These results suggest that concomitant expression of P102L with wild-type Smad4 inhibits the DNA-binding ability of wild-type Smad4 to SBE. Because Smad4-induced transcription from the PAI-1 promoter is dependent on binding to SBE (Stroschein et al, 1999), these ®ndings account for the mechanism whereby the P102L mutant acts as a dominant negative inhibitor of wild-type Smad4 in the transcriptional response assays (Figure 3a).…”
Section: Analyses Of the Dna-binding Ability Of Smad4p102lmentioning
confidence: 95%
See 1 more Smart Citation
“…Flag-and/or HA-tagged Smads and SnoN were isolated from transfected 293T cells by immunoprecipitation with anti-Flag (Sigma) or anti-HA agarose, followed by elution with Flag or HA peptide as described previously (Zhou et al 1998a;Stroschein et al 1999a). To detect endogenous APC associated with the Smads, nuclear extracts were prepared from 293T cells transfected with Flag-tagged Smad as described previously (Lee et al 1987), and the Flag-tagged protein was isolated by immunoprecipitation with anti-Flag agarose (Sigma), followed by elution with the Flag peptide as described previously (Zhou et al 1998a;Stroschein et al 1999a).…”
Section: Immunoprecipitation and Western Blottingmentioning
confidence: 99%
“…To detect endogenous APC associated with the Smads, nuclear extracts were prepared from 293T cells transfected with Flag-tagged Smad as described previously (Lee et al 1987), and the Flag-tagged protein was isolated by immunoprecipitation with anti-Flag agarose (Sigma), followed by elution with the Flag peptide as described previously (Zhou et al 1998a;Stroschein et al 1999a). Associated Cdc27 and Cdcl6 were detected by Western blotting with anti-Cdc27 and anti-Cdcl6.…”
Section: Immunoprecipitation and Western Blottingmentioning
confidence: 99%